1985
DOI: 10.1073/pnas.82.7.2077
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms determining aerobic or anaerobic growth in the facultative anaerobe Salmonella typhimurium.

Abstract: We isolated mutant strains of the facultative anaerobe Salmonella typhinuinum that grow either aerobically or anaerobically. Strict anaerobic mutants contained a defective DNA topoisomerase I gene (topi), while strict aerobic mutants contained a defective DNA gyrase subunit A gene (gyrA, also naLA). Topoisomerase I activity was detected in cell-free extracts of strict aerobic mutants but not of strict anaerobic mutant strains, whereas gyrase activity was detected in extracts of strict anaerobic mutants but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(90 citation statements)
references
References 30 publications
5
83
0
1
Order By: Relevance
“…Aside from its response to osmotic stress, DNA supercoiling was also involved in the regulation of anaerobic gene expression (13,32,33,52). The relationship between gyrasedependent and FNR-dependent anaerobic regulation has been observed by investigators in different laboratories.…”
Section: Discussionmentioning
confidence: 97%
“…Aside from its response to osmotic stress, DNA supercoiling was also involved in the regulation of anaerobic gene expression (13,32,33,52). The relationship between gyrasedependent and FNR-dependent anaerobic regulation has been observed by investigators in different laboratories.…”
Section: Discussionmentioning
confidence: 97%
“…One mechanism that may be responsible for this effect is the contribution of DNA supercoiling on P2 transcription during anaerobic vs. aerobic conditions. Studies with gyrase and topoisomerase mutants showed that the DNA in anaerobically grown cells is more highly supercoiled than in aerobically grown cells (Yamamoto and Droffner, 1985). Expression of the proU, tonB and fdhH genes has been shown to be directly influenced by the degree of DNA supercoiling (Axley and Stadtman, 1988;Dorman et al, 1988;Higgins et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data demonstrating a response at the level of DNA supercoiling to variations in pH (Bang et al 2002;Karem and Foster 1993;Quinn et al 2014), temperature (Goldstein and Drlica 1984), osmotic pressure (Alice and Sanchez-Rivas 1997; Bordes et al 2003;Cheung et al 2003;Higgins et al 1988;Meury and Kohiyama 1992;O'Byrne et al 1992;Sheehan et al 1992), oxygen supply (Bebbington and Williams 2001;Cameron et al 2011Cameron et al , 2013Cortassa and Aon 1993;Dixon et al 1988;Dorman et al 1988;Malkhosyan et al 1991;Yamamoto and Droffner 1985), oxidative stress (Weinstein-Fischer et al 2000), nutrition (Balke and Gralla 1987), growth phase (Bordes et al 2003;Conter et al 1997), intracellular growth (Ó Cróinín et al 2006) and much more have been reported. A rapidly growing cell has different gene expression requirements to one that is in stationary phase and one that is undergoing a growth phase transition has yet another set of needs.…”
Section: An Environmentally Responsive Global Regulatory Systemmentioning
confidence: 99%